PC based data logger / Mohd Hidzham Mohd Yusof - Mohd Yusof, Mohd Hidzham (2008)
This project was designed to facilitate the monitoring of the temperature from a remote location. The project contains hardware for sensing element and software Visual Basic 6 to create GUI that can monitoring and record the process. Serial port is use to communicate between hardware and software The central unit, personal computer then reads the data and displays the current temperature on the screen